Exercise for chronic musculoskeletal pain: a biopsychosocial approach - Booth, John; Schiltenwolf, Marcus (Musculoskeletal care, 2017)
Abstract: Chronic musculoskeletal pain (CMP) refers to ongoing pain felt in the bones, joints and tissues of the body that persists longer than 3 months. For these conditions, it is widely accepted that secondary pathologies or the consequences of persistent pain, including fear of movement, pain catastrophizing, anxiety and nervous system sensitization appear to be the main contributors to pain and disability. While exercise is a primary treatment modality for CMP, the intent is often to improve physical function with less attention to secondary pathologies. Exercise interventions for CMP which address secondary pathologies align with contemporary pain rehabilitation practices and have greater potential to improve patient outcomes above exercise alone. Biopsychosocial treatment which acknowledges and addresses the biological, psychological and social contributions to pain and disability is currently seen as the most efficacious approach to chronic pain. This clinical update discusses key aspects of a biopsychosocial approach concerning exercise prescription for CMP and considers both patient needs and clinician competencies. There is consensus for individualized, supervised exercise based on patient presentation, goals and preference that is perceived as safe and non?threatening to avoid fostering unhelpful associations between physical activity and pain. The weight of evidence supporting exercise for CMP has been provided by aerobic and resistance exercise studies, although there is considerable uncertainty on how to best apply the findings to exercise prescription. In this clinical update, we also provide evidence?based guidance on exercise prescription for CMP through a synthesis of published work within the field of exercise and CMP rehabilitation.